2012
DOI: 10.1029/2011ja017121
|View full text |Cite
|
Sign up to set email alerts
|

Study of the North West Cape electron belts observed by DEMETER satellite

Abstract: [1] We analyzed observation data collected by the Instrument for the Detection of Particles (IDP) on board the DEMETER satellite during a period of 17 months in 2007 and 2008. In the meantime, the VLF transmitter located at North West Cape (NWC) ground station was shut down during 7 months and working for a total of 10 months. By an (on-off) method, our analysis for the first time revealed in detail the transient properties of the space electron precipitation belt which is induced by the man-made VLF wave emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 27 publications
6
31
1
Order By: Relevance
“…The MSK bandwidth necessarily covers the entire spectrum over a ∼200 Hz range. NWC is currently the only significant VLF transmitter south of the equator, but may also have the most impact on the radiation belts due in large part to its location [ Kulkarni et al , 2008; Li et al , 2012]. In many of the subsequent figures, we thus focus on NWC as a representative example due to the particularly intense signal (1 MW radiated power) and resulting high SNR.…”
Section: Observationsmentioning
confidence: 99%
“…The MSK bandwidth necessarily covers the entire spectrum over a ∼200 Hz range. NWC is currently the only significant VLF transmitter south of the equator, but may also have the most impact on the radiation belts due in large part to its location [ Kulkarni et al , 2008; Li et al , 2012]. In many of the subsequent figures, we thus focus on NWC as a representative example due to the particularly intense signal (1 MW radiated power) and resulting high SNR.…”
Section: Observationsmentioning
confidence: 99%
“…Ground‐based VLF transmitters have been utilized for long‐distance communication and geo‐location in past decades (Swanson, ; Watt, ) and can penetrate through the ionosphere and propagate within the plasmasphere. The related ionosphere disturbances, particle precipitation, wisp electron precipitation structure (Sauvaud et al, ), heating phenomenon, and wave propagation have also been studied (Bell et al, ; Cohen & Inan, ; Gamble et al, ; Graf et al, ; Inan et al, ; Li et al, ; Marshall et al, ; Parrot et al, , ; Starks et al, ; Tao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars (Sauvaud et al, ; Gamble et al, ; Li et al, ) have studied the electron precipitation phenomenon—the two easterly‐westerly stripes at middle latitudes in both the northern and southern hemispheres (Figure ), which appear as wisp structures in the orbital energy spectrum. The number of electrons with energy between 100 and 600 keV are obviously increased, which tallies with the theory of linear wave‐particle interaction.…”
Section: Electron Precipitation Excited By Man‐made Vlf Em Wavesmentioning
confidence: 99%
“…With the rapid development of satellite exploring technology, it has been determined from satellite observations that man‐made ground sources can definitely cause energetic particle precipitation in space. Some examples are: the EXOS‐B satellite observed the 0.3–6.9 keV electron flux anomaly caused by the electromagnetic waves of 0.3–9 kHz from the SIPLE station (Kimura et al, ); the low‐probability electron flux anomaly created by switching on/off the NPM transmitter was observed by the DEMETER satellite (Inan et al, ; Graf et al, ); and the DEMETER satellite also observed the electron precipitation belt ( L =1.4–1.7) correlated to the Australian NWC transmitter (Li XQ et al, ).…”
Section: Introductionmentioning
confidence: 99%